Analysis of the effects of chemical ageing of ethylene-propylene diene monomer by chemical, spectroscopic, and thermal means. (February 2018) - McDonnell, Darren; Balfe, Nora; O'Donnell, Garret E.
Abstract: Ethylene-propylene diene monomer (EPDM) failures due to material degradation poses a major risk in the biopharmaceutical industry, which can result in long periods of production downtime. It is suspected that a key cause of this EPDM degradation is due to the chemical solutions used in equipment cleaning processes, resulting in crosslinking of the EPDM polymer bulk. However, the mechanisms responsible for crosslink formation, and whether other degradation sources are also present, has never been investigated in the public domain. Twenty four virgin samples were utilised for testing, twelve of which were subject to common chemical cleaning solutions used in the biopharmaceutical sector. The chemical solutions under investigation were aqueous solutions of NaOH, NaClO, H3 PO4, and the interaction between 100 °C H2 O and NaClO. The characterisation of the degradation process was conducted via chemical, spectroscopic and thermal means. The results show that degradation of the polymer bulk proceeds predominantly via crosslinking for all exposure types, due to oxidative damage and the formation and recombination of free radicals. Loss of plasticiser in the polymer matrix and thermo-oxidative damage are contributory degradation mechanisms. NaOH and H3 PO4 exposure results in an accelerated rate of crosslinking compared to NaClO in the early stages of exposure. Highlights: Ethylene-propylene diene monomer parts exposed to NaOH, NaClO, and H3 PO4 solutions. Crosslinking is the dominant degradation mechanism present. Oxidative damage occurs in polymer bulk due to chemical exposure. Carboxylate and hydroxyl group formation responsible for crosslink formation. Loss of plasticiser and thermo-oxidative damage contributory degradation mechanisms.